2011
DOI: 10.3892/ol.2011.254
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan reduces the toxicities of chemotherapy for patients with unresectable advanced or recurrent colorectal cancer

Abstract: Abstract. Combination chemotherapy with oxaliplatin plus 5-fluorouracil/leucovorin (FOLFOX) or irinotecan plus 5-fluorouracil/leucovorin (FOLFIRI) has become a standard regimen for advanced or recurrent colorectal cancer. Numerous studies have reported that long-term use of FOLFOX or FOLFIRI leads to better survival for these patients. Thus, control of the toxicity of these drugs may be crucial to prolonging survival. Fucoidan is one of the major sulfated polysaccharides of brown seaweeds and exhibits a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 16 publications
1
76
2
1
Order By: Relevance
“…It has also become the center of much attention because of its anti-cancer activity and is expected to be a new candidate for low-toxicity cancer therapy [39], [40]. The Ups-fucoidan we extracted from the U. pinnatifida sporophylls had higher sulfate content and better activities than that from other U. pinnatifida segments [24], [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has also become the center of much attention because of its anti-cancer activity and is expected to be a new candidate for low-toxicity cancer therapy [39], [40]. The Ups-fucoidan we extracted from the U. pinnatifida sporophylls had higher sulfate content and better activities than that from other U. pinnatifida segments [24], [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently was demonstrated that patients with colorectal cancer under chemotherapeutic treatment with oxaliplatin/5-fluorouracil/leucovorin or irinotecan/ fluorouracil/leucovorin may benefit from a co-treatment with fucoidan. Decrease of some adverse effects, such as general fatigue, and a tendency to increase survival rate was reported in the group of patients that received fucoidan (Ikeguchi et al, 2011).…”
Section: Fucoidanmentioning
confidence: 95%
“…In the present study, we used a high-molecular-weight product of fucoidan derived from Cladosiphon okamuranus (Okinawa mozuku) by Marine Products Kimuraya Co., Ltd. (Tottori, Japan). In the fucoidan group, every patient took 150 mL/day of liquid that contained 4.05 g fucoidan for 6 months after commencing chemotherapy [5].…”
Section: Fucoidan Treatmentmentioning
confidence: 99%
“…Previously, we reported that fucoidan could reduce the toxicity of combination chemotherapy with oxaliplatin plus 5-fluorouracil (5-FU)/leucovorin (LV) (FOLFOX) or irinotecan plus 5-FU/LV (FOLFIRI) for patients with advanced colorectal cancer [5]. Fucoidan is a sulfated polysaccharide that is found in various species of brown seaweed, such as kombu, wakame, mozuku, and hijiki.…”
Section: Introductionmentioning
confidence: 99%